Trump Impeachment Aftermath : Implications for Global Politics and Security - Garfinkle, Adam (2020)
The US impeachment ordeal has left American political culture worse off on balance. It has had the concomitant effect of deepening and accelerating the inward turn of US foreign and national security policy.